Hypothesis on the Role of Cryptochromes in Inflammation and Subarachnoid Hemorrhage Outcome - Nogueira, Adriano Barreto; Nogueira, Ariel Barreto; Veiga, José Carlos Esteves; Teixeira, Manoel Jacobsen (Frontiers in Neurology, 2017)
We have recently found that the temperature variability (TV) in the day-night cycle may predict the mean intracranial pressure in the following 24 hours (ICP24) in subarachnoid hemorrhage patients under multimodality monitoring, sedation, and hypothermia (T<35°C). Specifically, we found that ICP24 = 6(4 – TV) mmHg. TV is the ratio between the coefficient of variation of temperature during the nocturnal and the preceding diurnal periods. This result suggests that the circadian clock reflects brain plasticity mechanisms and its malfunctioning leads to deterioration of the neurologic status. The sleep-wake cycle is absent in these patients and their circadian clock can function properly only by environment light-independent mechanisms. One mechanism involves the circadian clock proteins named cryptochromes. Cryptochromes are highly preserved and widespread in the evolutionary tree, are expressed in different cell types in humans (type II cryptochromes, in two forms: human cryptochrome 1 and 2 (hCRY1 and hCRY2)), and in certain species respond to blue light and play role in magnetoreception. Interestingly, subarachnoid hemorrhage outcome seems to correlate with inflammation, and cryptochromes decrease inflammatory activity. Our hypothesis derived from these observations is that cryptochromes modulate the circadian oscillation of temperature even during therapeutic hypothermia and improve outcome in subarachnoid hemorrhage through decrease in inflammation. A strategy to test this hypothesis is to measure periodically during the acute phase of high-grade subarachnoid hemorrhage the level of cryptochromes in cerebrospinal fluid and circulating white blood cells, and to correlate these levels with outcome, TV, ICP24, and pro- and anti-inflammatory markers in cerebrospinal fluid and blood. If this hypothesis is true, the development of therapies targeting inflammation in subarachnoid hemorrhage could take advantage of cryptochrome properties. It has been shown that blue light phototherapy increases the expression of cryptochromes in blood mononuclear cells in jaundiced neonates. Likewise, visual stimulus with flashing light improves Alzheimer’s disease features in experimental model and there is a prominent expression of cryptochromes in the retina. Remarkably, recent evidence showed that hCRY2 responds to electromagnetic fields, which could be one elusive mechanism of action of transcranial magnetic stimulation and a reason for its use in subarachnoid hemorrhage.